The Common Acute Injuries & Their Management Among Inter-University Female Volleyball Players Throughout Bangladesh - Siddiqui, Muhammad Sakib Sad; Bowm, Milton (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2025)
This study looks at the injury rate, causes, and coping mechanisms of female intercollegiate volleyball players. The subjects were thirty female gamers. Among athletes from several institutions, a cross-sectional survey was carried out to gather information on injury kinds, frequency, causes, and treatment. According to the results, the most frequent acute injuries include ankle sprains, finger dislocations or fractures, shoulder injuries, hand injuries, and knee ligament injuries. Strength training, flexibility exercises, appropriate footwear, and proper landing technique are all factors that increase the risk of injury. The results show that because of inadequate training, inadequate medical care, and poor skill levels, athletes cannot afford the right kind of training to perform at a high level.